Enhancing the uniqueness of Taman Herba Perak through healing landscape concept. Case study : Gopeng, Perak - Azamuddin, Nur Ezzayani (2018)
Today, in Malaysia healthcare facilities is not the choice to apply at any green space in term of improving a living quality among the users. However when referring to the two of the goals in Sustainable Goals Development (SDG), which is the first goals is “Good health and well being”. This goal a remain to evoke the healthy lives by promoting the well-being for all ages. Next is “Life on land” means we need to take an initiative to avoid biodiversity loss and protect the home indigenous population. Based on those goals, through a collection of data and information that has been collected during the site visit, there are several issues that might be a potential to solve using the healing landscape at Taman Herba Negeri Perak. The issues of this site study that related to the connectivity between place to another place within the nature area caused by the lack of attractive activity that contributes to the unutilized space. The author decided to rebrand Taman Herba Negeri Perak incorporated with the healing landscape concept for community attachment and liveliness in nature by applying the concept through the educational, experiential and recreational space at this site study. The communal activity among the community will generate the economic to proposed a place of liveliness in nature to increase the quality of life. By applying all those idea and concept, it might be attracting the interior user and then will contribute to spread among the exterior user. This process from the visitation activity that will transform become a tourism spot in Perak Darul Ridzuan by using a healing approach into the design of site study. In this study also discussed the importance of the mode and senses of human through the healing landscape elements. Healing landscape element will contribute user experience nature while doing a learning process in term of various actions. Questionnaires distributed through the Taman Herba Negeri Perak to gained more evidence and identify the users’ needs and applied to the design.